2023
DOI: 10.3390/cancers15133331
|View full text |Cite
|
Sign up to set email alerts
|

Association of Myelofibrosis Phenotypes with Clinical Manifestations, Molecular Profiles, and Treatments

Abstract: Myelofibrosis (MF) presents an array of clinical manifestations and molecular profiles. The two distinct phenotypes− myeloproliferative and myelodepletive or cytopenic− are situated at the two poles of the disease spectrum and are largely defined by different degrees of cytopenias, splenomegaly, and distinct molecular profiles. The myeloproliferative phenotype is characterized by normal/higher peripheral blood counts or mildly decreased hemoglobin, progressive splenomegaly, and constitutional symptoms. The mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 163 publications
(301 reference statements)
0
3
0
1
Order By: Relevance
“…Thrombosis imposes a substantial morbidity burden on MF patients [42,43] and mandates the introduction of specific therapies that may further make it difficult to optimize care [44]. Myelodepletive phenotype, low platelet count and developed complications of portal hypertension that are encountered in subsets of MF patients further challenge the delivery of specific primary and secondary prevention measures [45][46][47][48][49][50]. Thrombosis also significantly increases healthcare resource utilization and treatment costs [51], which are already high in patients with MF [52].…”
Section: Discussionmentioning
confidence: 99%
“…Thrombosis imposes a substantial morbidity burden on MF patients [42,43] and mandates the introduction of specific therapies that may further make it difficult to optimize care [44]. Myelodepletive phenotype, low platelet count and developed complications of portal hypertension that are encountered in subsets of MF patients further challenge the delivery of specific primary and secondary prevention measures [45][46][47][48][49][50]. Thrombosis also significantly increases healthcare resource utilization and treatment costs [51], which are already high in patients with MF [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, the biologic ramifications and phenotypic associations with mutation profiles, particularly the impact of additional mutations in individuals with the same driver mutation, remain poorly understood. Studies have indicated that a higher allelic burden of JAK2 V617F and type 2 CALR mutations is correlated with elevated blood cell counts (reviewed by Chifortides et al [50]). A study by Grinfeld et al on 2035 MPN patients suggested that genetic mutations and germline polymorphisms contribute, at least partially, to the determination of the phenotype [25].…”
Section: Additional Mutationsmentioning
confidence: 99%
“…Fedratinib presents a possible option for MF patients who are refractory/intolerant to ruxolitinib [ 74 ]. Importantly, there was a critical unmet need for MF patients with cytopenias prior to the regulatory approval of pacritinib and momelotinib, the preferable non-myelosuppressive JAK inhibitors to treat cytopenic patients with MF [ 75 ], because both ruxolitinib [ 60 , 76 ] and fedratinib [ 77 ] may worsen cytopenias.…”
Section: Concurrent Acvr1 and Jak Inhibition In Myelofibrosismentioning
confidence: 99%